Pengaruh Keteladanan Guru Pendidikan Agama Kristen terhadap Karakter Peserta Didik Kelas X SMK Negeri 1 Raya Kabupaten Simalungun Tahun Pembelajaran 2023/2024 - Marice Simamora; Johari Manik; Hasudungan Simatupang; Sandy Ariawan; Ordekoria Saragih (Jurnal Magistra, 2024)
The purpose of this study was to determine the positive and significant influence of the Exemplary Christian Education Teacher on the Character of Class X Students of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year. The research method used was a quantitative method with descriptive statistics. The population was 159 Protestant Christian students of class X of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year and a sample of 40 people was determined using a random sampling technique. Data were collected using a positive closed questionnaire of 39 items, namely 20 items for variable X and 19 items for variable Y. The results of the data analysis showed that there was a positive and significant influence of the Exemplary Christian Religious Education Teachers on the Character of Class X Students of SMK Negeri 1 Raya, Simalungun Regency in the 2023/2024 Academic Year, as evidenced by the following data analysis: 1) Analysis requirements test: a) Positive relationship test obtained rxy value = 0.479> rtable ( = 0.05, n = 40) = 0.312. b) Significant relationship test obtained tcount = 3.364> ttable ( = 0.05, dk = n-2 = 38) = 2.021. 2) Influence test: a) Regression equation test Y ̂="2.85" + 0.79X. b) Regression determination coefficient test (r2) = 22.9%. 3) Hypothesis testing using the F test obtained Fcount > Ftable = ( = 0.05, df numerator k = 13, df denominator = n-2 = 40-2 = 38) which is 11.3 > 2.00. Thus Ha is accepted and H0 is rejected.